1994
DOI: 10.1113/jphysiol.1994.sp020365
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic asymmetries of cardiac output transients in response to muscular exercise in man.

Abstract: 1. We determined the kinetics of cardiac output (Q) with respect to oxygen uptake (Po2) at the on-and off-transients of constant-load exercise. Six subjects performed constantload exercise which consisted of 5 min rest, 5 min one-legged pedalling at 50 W and a 5 min recovery period. 2. The transient responses were characterized by first-order kinetics. There was no significant difference between the time constants for VPo (TV,) at the on-(33 9 + 3-5 s, mean + S.E.M.) and off-transient (37-2 + 2-9 s). The time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
70
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 27 publications
7
70
2
Order By: Relevance
“…Some authors, however, soon identified two components of the V O 2 kinetics: 1) a rapid, almost immediate phase (phase I) (5,54,55), which they attributed to an immediate increase in cardiac output (Q ) at exercise start; and 2) a subsequent slower phase (phase II), to which they restricted the influence of muscle metabolic adjustments. The strongest support to this view came from the demonstration that the kinetics of Q (12,13,16,60) and arterial O 2 flow (Q a O 2 ) (27) are very rapid.…”
mentioning
confidence: 85%
“…Some authors, however, soon identified two components of the V O 2 kinetics: 1) a rapid, almost immediate phase (phase I) (5,54,55), which they attributed to an immediate increase in cardiac output (Q ) at exercise start; and 2) a subsequent slower phase (phase II), to which they restricted the influence of muscle metabolic adjustments. The strongest support to this view came from the demonstration that the kinetics of Q (12,13,16,60) and arterial O 2 flow (Q a O 2 ) (27) are very rapid.…”
mentioning
confidence: 85%
“…This view restricts the correspondence between lung O 2 uptake and muscle O 2 consumption to the monoexponential phase II. Perhaps the strongest piece of evidence in support of the phase I concept is the finding that the kinetics of cardiac output (Q ) upon light exercise onset is much faster than that of V O 2 (12,14,21,34,38,59,60). In fact, assuming invariant O 2 concentration in mixed venous blood in the first seconds of exercise, this finding would imply, according to the Fick principle, a corresponding rapid increase in V O 2 .…”
mentioning
confidence: 94%
“…O 2 at the onset of exercise. [27,33,34] In addition, during the stimulation at 70% of V . O 2max the O 2 partial pressure (PaO 2 ) in isolated dog muscle is always above 2mm Hg, the critical level for maintaining aerobic ATP turnover.…”
Section: O 2 Utilisationmentioning
confidence: 99%